Intercropping of wheat alleviates the adverse effects of phenolic acids on faba bean - Zheng, Yiran; Guo, Yuting; Li, Yu; Yang, Wenhao; Dong, Yan (Frontiers in Plant Science, 2022)
Abstract After years of continuous cultivation of faba beans (Vicia faba L.), autotoxic substances accumulate in the soil, leading to a high incidence of Fusarium wilt (FOF). Faba bean-wheat intercropping is often used to alleviate these problems. The goal of this research was to explore the role of benzoic acid and cinnamic acid in promoting the occurrence of faba bean Fusarium wilt and the potential mechanism of faba bean-wheat intercropping to control the occurrence of this disease. We established a field experiment and a hydroponic experiment that involved the inoculation of FOF and the exploration of exogenous addition of cinnamic acid and benzoic acid at different concentrations, the effects on the degree of peroxidation, resistance system and ultrastructure of faba bean roots. In addition, the antioxidative response of faba bean-wheat intercropping against the autotoxicity of benzoic acid and cinnamic acid was examined. In the field experiment, compared with monoculture, faba bean -wheat intercropping effectively controlled the occurrence of Fusarium wilt, significantly reduced the contents of H2O2 and O2- in faba bean roots, increased the expression and activity of antioxidant enzymes SOD and CAT, maintained cell stability, and significantly reduced the contents of benzoic acid and cinnamic acid in faba bean rhizosphere. In the pot experiment, it was found that compared with the control, different concentrations of benzoic acid and cinnamic acid (50 mg.L-1, 100 mg.L-1, and 200 mg.L-1) significantly increased the content of H2O2 and O2- in faba bean, decreased the activity and gene expression of antioxidant enzymes SOD and CAT, and damaged cell membrane structure. Furthermore, it promoted the occurrence of Fusarium wilt of faba bean. The faba bean-wheat intercropping alleviated the stress .Benzoic acid and cinnamic acid can increase the content of hydrogen peroxide and superoxide anions in faba bean plants, reduce the enzymatic activity and expression of antioxidant enzyme genes, damage the cell membrane structure and promote the occurrence of faba bean Fusarium wilt. The faba bean-wheat intercropping can effectively alleviate the autotoxicity of benzoic acid and cinnamic acid and reduce the occurrence of faba bean fusarium wilt.